Socialism in Education: Propaganda of Political Parties in Nepal (Tri-Chandra Journal of Anthropology, 2024)
Mainstream political Parties have officially adopted the notion of socialism, also recognized in the constitution of Nepal, 2072. However, the commitment towards socialism is not in tandem with the practical considerations because of their attachment and penetration with neo-liberal policy. This paper aims to explore why state and political parties unlike their declared commitment towards state-sponsored education system tend to privatization and the role of political parties in this regard. The study is purely qualitative and it employs content analysis as the tool of collecting data. The finding of the study is that adaptation of neo-liberal policy in education system in Nepal contributes in supporting the privatization of educational institutions, creating two different layer of education.